Streamyx complaint by customers: a case study in Telekom Malaysia Berhad Melaka / Nur Syahirah Mahassan - Mahassan, Nur Syahirah (Faculty of Business and Management, 2011)
The purpose of this study is to identify what are the problems that have been faced by customers when using Streamyx since it was launched in 200, what are the causes of those problems happen and also to observe what are the action taken by Telekom Malaysia to overcome complains and to suggest the alternative way to overcome such complaints that reported by customers. Based on the information gathering and the There are 8 type of complain that have been reported by the customers such as difficult to connect (DSL blinking, DSL off), cannot browse, Error 691-Invalid login ID or password, Error-678-Remote computer did not respond, frequent disconnection/ intermittent, noisy telephone line, slow internet connection as compared to package subscribe and also complain on service quality, and termination not satisfied with services. All the problems that have been faced by customers result from the several causes includes of faulty hardware, suspension of account, incorrect parallel telephone setting, telephone line quality, Internet Service provider network problem and so on.